PENGARUH KONSUMSI KAFEIN KOPI FILTER ARABIKA DALAM PEMBELAJARAN PENDIDIKAN JASMANI TERHADAP TINGKAT KEBUGARAN JASMANI SISWA SEKOLAH MENENGAH ATAS NEGERI 1 DRAMAGA - Muliawan, Muhamad Wijdan Hilmy; Mahardhika, Dhika Bayu; Hidayat, Abdul Salam (Universitas Hamzanwadi, 2024)
This study aims to determine the effect of caffeine in coffee on the level of physical fitness in students. Pre-experimental research with one group pretest posttest design. This sample was selected by purposive sampling, respondents carried out normal learning activities for 8 meetings with the first pretest using the Indonesian student physical fitness test instrument without giving coffee, after that learning according to the lesson plan for 6 meetings with the treatment of giving coffee one hour before learning and posttest with the same test instrument as the first meeting with coffee. The results of the pretest and posttest data analysis were carried out with the T-Test (Paired Sample Test) test. The fitness value of respondents after the stimulus using coffee showed an increase. The conclusion of this study is that the results of the value of the posttest from each test instrument have the results of the paired sample T-test test value with the